CORRELATION BETWEEN DEGREES OF HYPERTENSION AND COGNITIVE FUNCTION IN ELDERLY PEOPLE IN BANYUATES VILLAGE SAMPANG MADURA - Intan Maryana Salzabillah; Dyana Sarvasti; Inge Wattimena (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2023)
Background: Hypertension was the first of the ten most common diseases in the elderly in 2013. Data from the World Health Organization (WHO) in 2015 showed that around 1.13 billion people had hypertension, meaning that 1 in 3 people worldwide was diagnosed with hypertension. Objective: To examine the correlation between the degree of hypertension and cognitive function in the elderly in Banyuates Village, Sampang Madura.Methods: This research is an observational analytic study with a cross-sectional approach. The sampling technique is purposive sampling. The correlation test for the two variables was carried out using the Spearman test. The correlation between variables is considered significant if the p-value <0.05 is obtained.Results: The correlation between the degree of hypertension and cognitive function in the elderly was statistically significant (p= 0.000). The correlation value of -0.732 indicates a significant negative correlation between the degree of hypertension and cognitive function.Conclusion: The results of this study indicate that most of the older people studied suffer from grade 1 hypertension and abnormal cognitive function. There is a significant negative correlation between the degree of hypertension and cognitive function. The discourse of this research can be socialized in health promotion/education for older people to control their blood pressure, which tends to be high, to have reasoning power and good quality of life.